2021
DOI: 10.1016/j.ijrobp.2020.10.024
|View full text |Cite
|
Sign up to set email alerts
|

The Risk of Subclinical Breast Cancer-Related Lymphedema by the Extent of Axillary Surgery and Regional Node Irradiation: A Randomized Controlled Trial

Abstract: Purpose: To compare the risk of subclinical breast cancererelated lymphedema (sBCRL) using bioimpedance spectroscopy (BIS) or tape measure (TM) by the extent of axillary surgery and regional nodal irradiation (RNI). Methods and Materials: Patients were randomized to surveillance with TM or BIS. A BIS !6.5 L-Dex units or TM volume change !5 and <10% above presurgical baselines "triggered" sBCRL. The incidence of sBCRL by sentinel node biopsy or axillary lymph node dissection (ALND) with or without RNI was exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
1
10
1
Order By: Relevance
“…Regarding treatment, patients undergoing ALND, RNI, and taxane‐based chemotherapy remain at higher risk for chronic lymphedema than others do, even after receiving a preventive compression intervention at onset of subclinical lymphedema. The ALND and RNI findings are consistent with previous research that found less treatment to the axilla (sentinel node biopsy alone) was associated with less incidence of subclinical BCRL than more extensive treatment (ALND or radiation that included level 3 of the axilla or supraclavicular fossa) 47 . The taxane finding is not surprising because taxane‐based chemotherapy was the predominant chemotherapy administered in this study, yet these results contrast with findings from another large prospective study in this population in which taxane‐based chemotherapy was not found to be a risk factor 48 .…”
Section: Discussionsupporting
confidence: 90%
“…Regarding treatment, patients undergoing ALND, RNI, and taxane‐based chemotherapy remain at higher risk for chronic lymphedema than others do, even after receiving a preventive compression intervention at onset of subclinical lymphedema. The ALND and RNI findings are consistent with previous research that found less treatment to the axilla (sentinel node biopsy alone) was associated with less incidence of subclinical BCRL than more extensive treatment (ALND or radiation that included level 3 of the axilla or supraclavicular fossa) 47 . The taxane finding is not surprising because taxane‐based chemotherapy was the predominant chemotherapy administered in this study, yet these results contrast with findings from another large prospective study in this population in which taxane‐based chemotherapy was not found to be a risk factor 48 .…”
Section: Discussionsupporting
confidence: 90%
“…The compression sleeve prescription used in this trial was tailored to prevent accumulation of extracellular fluid arising from surgery, adjuvant chemotherapy, and radiotherapy. 42,47 and to address gravitational forces that occur while in the upright position. 48 These parameters appeared to be well tolerated, as indicated by the lack of any negative effect on patient-reported outcomes, including arm symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…As BIS quantifies the extracellular fluid, of which lymph is a component, the higher incidence of swelling detected by BIS is expected. 41,42 The prophylactic use of compression sleeves reduced the incidence of arm swelling to the clinically meaningful target, ie, a reduction of 10% set a priori.…”
Section: Discussionmentioning
confidence: 99%
“…An additional concern regarding more comprehensive coverage of nodal tissue is that it may result in increased lymphoedema toxicity, as previously reported. 18,30 Indeed, the ESTRO guidelines state that an increase in treated volume (beyond old simulator based fields) should be avoided as 'no clinical reason for this exists, and as this might lead to an increase in the dose to OARs'. 9 In addition, it is possible that the use of apical clips might add to surgical toxicity, although we have not noted this, and it might be difficult to evaluate.…”
Section: Discussionmentioning
confidence: 99%